Using Prosopography to Raise the Voices of Those Erased in Social Work History. Issue 1 (February 2018) - Coles, D. Crystal; Netting, F. Ellen; O'Connor, Mary Katherine
In this article, we introduce prosopography, a valuable historical research method that can be used by feminist social work scholars. While feminists in various fields use this methodology to investigate background characteristics of women in history through collective studies of how they have established relationships and networks to influence change, our review of the literature suggests that it has been little used in social work. We provide a brief overview of prosopography, strengths and limitations, and an illustration of the method as enacted focusing on the roles of early feminists within the development of nonprofit human service organizations. It is our intent to demonstrate the possibilities of prosopography to identify and understand groups of women who have been erased in social work history.